Seed predation selects for reproductive variability and synchrony in perennial plants. Issue 4 (19th August 2020) - Bogdziewicz, Michał; Szymkowiak, Jakub; Tanentzap, Andrew J.; Calama, Rafael; Marino, Shealyn; Steele, Michael A.; Seget, Barbara; Piechnik, Łukasz; Żywiec, Magdalena
Summary: Annually variable and synchronous seed production by plant populations, or masting, is a widespread reproductive strategy in long‐lived plants. Masting is thought to be selectively beneficial because interannual variability and synchrony increase the fitness of plants through economies of scale that decrease the cost of reproduction per surviving offspring. Predator satiation is believed to be a key economy of scale, but whether it can drive phenotypic evolution for masting in plants has been rarely explored. We used data from seven plant species ( Quercus humilis, Quercus ilex, Quercus rubra, Quercus alba, Quercus montana, Sorbus aucuparia and Pinus pinea ) to determine whether predispersal seed predation selects for plant phenotypes that mast. Predation selected for interannual variability in Mediterranean oaks ( Q. humilis and Q. ilex ), for synchrony in Q. rubra, and for both interannual variability and reproductive synchrony in S. aucuparia and P. pinea . Predation never selected for negative temporal autocorrelation of seed production. Predation by invertebrates appears to select for only some aspects of masting, most importantly high coefficient of variation, supporting individual‐level benefits of the population‐level phenomenon of mast seeding. Determining the selective benefits of masting is complex because of interactions with other seed predators, which may impose contradictory selective pressures. Abstract : See also the Commentary on this article by Kelly, 229 : 1829–1831 .